THE INFLUENCE OF INFRASTRUCTURE DEVELOPMENT ON LOCAL ECONOMIC GROWTH IN MEDAN - Jonson Rajagukguk (The American Journal of Interdisciplinary Innovations and Research, 2024)
Research Objectives The aim of this research is to determine and analyze the extent to which GRDP and investment variables influence local economic growth in Medan City through increasing community income as an intervening variable . Originality The subject of this research is the population/community in Medan City, where the variables in this research are the independent variables, namely GRDP and investment , the dependent variable, namely the local economic growth variable in Medan City and the intervening variable is the community income variable . The results of data analysis used SEM analysis using SMART PLS 4.0 software. as for data collection techniques using questionnaires and interviews, as well as observation . Design/methodology/approach Method research using descriptive quantitative data analysis methods using the structural equation model (SEM) method, where the results of data processing using the SEM method are carried out using the PLS 4.0 application . Findings From the results of this research, the conclusions that exist are that partially the GRDP and investment variables have an influence on the local economic growth of Medan City and have an influence on the income of the people of Medan City. Simultaneously, the GRDP and investment variables influence the local economic growth of Medan City through the variable income of the people of Medan City as an intervening variable . Implementation The greater the factors that influence infrastructure development through investment and increasing GRDP, the more employment opportunities there will be and the people's income will increase, and will significantly increase economic growth in the city of Medan.